OPTIMALISASI STATUS KESEHATAN DENGAN SENAM LANSIA DI DESA BANDUNG - Shanti Rosmaharani; I'in Noviana (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Indonesia is one of the developing countries that has entered the era of the elderly structured population, it is estimated that the number of elderly people in 2035 will be 48.19 million. In the elderly will experience changes in the system in the body and the changes that occur will show a decrease in organ function. Actions that can be used to overcome this include elderly exercise. This community service aims to optimize health status with elderly exercise. This community service was carried out at Posbindu, Bandung Krajan Village and Posbindu Sumbersuko. The implementation method is carried out by direct practice, namely weighing, controlling blood pressure and implementing elderly gymnastics. This activity collaborates with nurses, village midwives and cadres, and is carried out with health protocols. The results of the activity obtained blood pressure for the elderly before and after the exercise. This activity was followed by the elderly who were very enthusiastic about participating in gymnastics. After following the elderly exercise, the elderly said their body felt more fit and fresh. In addition, some elderly also said that joint pain was reduced because they were actively moving.